Ocular Disease in Mice Inoculated with Pork Heart Samples Infected with Toxoplasma gondii. (17th February 2022) - Costa, Deise F.; Madeira, Rafael Pedro; Torrecilhas, Ana Claudia; Nascimento, Heloisa; Ribeiro, Kleber Silva; Paraboni, Marisa Lúcia Romani; Rizzo, Luiz Vicente; Silveira, Claudio; Burnier, Miguel N.; Lowen, Marcia Serva; Garcia, João Luis; Gava, Ricardo; et al.
ABSTRACT: Purpose: We analyzed the frequency, viability, and genetic characteristics of T. gondii in pork heart samples Methods: Thirty-five fresh pork samples were purchased in a slaughterhouse in Erechim city. The DNA was extracted and qPCR was performed. T. gondii genotyping was performed using PCR-RFLP analysis. Positive samples were digested and inoculated in mice for viability analysis. Results: Our results showed that T. gondii DNA was detected in 25.7% of the pork heart samples and genotyping revealed one new atypical strain. The viability analyses demonstrated that 40% of mice presented clinical signs of T. gondii infection. qPCR was positive in the lung, liver, and brain of mice that presented clinical signs of T. gondii infection. Also, the histopathology analysis showed retinal disorganization, retinal detachment, inflammatory cell infiltration, and fibrosis in the eyes analyzed. Conclusion: Our findings have shown that pork eat from southern Brazil may contain live T. gondii that could be associated with toxoplasmosis.